Perceptions And Motivation of Students in Learning Javanese Music Karawitan In Cultural Arts Learning At State Senior High School 1 Batu (SMA Negeri 1 Batu) - Hanun Adhaninggar; Soerjo Wido Minarto (International Research and Development for Human Beings (IRDH), 2024)
This research was done to describe several things, which include: (1) students' perceptions of learning Javanese music karawitan in cultural arts learning at SMA Negeri 1 Batu; (2) knowing the level of student motivation in learning Javanese music karawitan in cultural arts learning at SMA Negeri 1 Batu. This research is quantitative and descriptive. Data collection uses steps such as the preparation stage, implementation stage, data analysis preparation stage and data analysis techniques using percentage techniques, while the population and samples are carried out by Simple Random Sampling with a total sample of 52 students. The results of this study are the perception of students in learning Javanese musical music tends to be positive, and the level of motivation of students in learning Javanese musical music is quite high, this can be seen from the results of research on several aspects of positive results and student interest in learning Javanese musical music in Cultural Arts learning is relatively high to try to get good learning results.